2019
DOI: 10.1038/s41418-019-0328-3
|View full text |Cite
|
Sign up to set email alerts
|

TRAF4 positively regulates the osteogenic differentiation of mesenchymal stem cells by acting as an E3 ubiquitin ligase to degrade Smurf2

Abstract: TNF receptor-associated factor 4 (TRAF4), a member of the TRAF family, plays an important role in the embryogenesis and development of the bone system. Mesenchymal stem cells (MSCs), which are the primary origin of osteoblasts in vivo, are key cells in bone development; however, whether TRAF4 modulates the osteogenic capacity of MSCs has never been explored. In this study, we demonstrated that TRAF4 positively regulates the osteogenic process of MSCs both in vitro and in vivo. In addition, we further demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 48 publications
8
34
0
Order By: Relevance
“…Previous studies have demonstrated that the shift in preferential differentiation of MSCs from osteoblasts to adipocytes plays a role in the pathogenesis of osteoporosis via reducing bone mineral density [23]. We have already demonstrated that TRAF4 positively regulated the osteogenic differentiation of MSCs and TRAF4 was found to be abnormally decreased in osteoporosis specimen [14]. Thus, we hypothesis that TRAF4 not only regulate osteogenic differentiation of MSCs but also modulate the adipogenic capacity of MSCs.…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…Previous studies have demonstrated that the shift in preferential differentiation of MSCs from osteoblasts to adipocytes plays a role in the pathogenesis of osteoporosis via reducing bone mineral density [23]. We have already demonstrated that TRAF4 positively regulated the osteogenic differentiation of MSCs and TRAF4 was found to be abnormally decreased in osteoporosis specimen [14]. Thus, we hypothesis that TRAF4 not only regulate osteogenic differentiation of MSCs but also modulate the adipogenic capacity of MSCs.…”
Section: Introductionmentioning
confidence: 66%
“…reported that TRAF4 interacts with other proteins primarily through the RING domain or the TRAF domain [12,26]. Thus, we transfected plasmids encoding Myc-TRAF4 or deletion mutants (TRAF4 DRING or TRAF4 DTRAF) and Flag-PKM2 into 293T cells, which were then subjected to immunoprecipitation with an anti-Myc antibody and immunoblotting with an anti-Flag antibody.…”
Section: Traf4 Binds With Pkm2 Through the Ring Domain And N-and Ctermentioning
confidence: 99%
See 1 more Smart Citation
“…Fracture is very common in clinic, a rapid healing of fracture can help patient get early recovery, decrease the occurrence of certain related complications, as well as improving the quality of life. Osteoblast differentiation is vital during bone remodelling and fracture healing and is regulated by an array of biological factors . MC3T3‐E1 cells are precursors of osteoblasts, which are established from a C57BL/6 mouse calvaria and selected on the basis of high alkaline phosphatase (ALP) activity in the resting state .…”
Section: Introductionmentioning
confidence: 99%
“… 4 Accumulating evidence has suggested that induction of adipocyte differentiation impairs bone formation, while increased osteogenic differentiation is essential for bone mass increase. 5 , 6 , 7 Therefore, a clear understanding of MSC fate regulation is required. Recent studies have focused on investigating the regulation of extrinsic and intrinsic regulators on MSC fate.…”
Section: Introductionmentioning
confidence: 99%